The Effect of Profitability and Deviden Policy on Company Value (Case Study in the Healthcare Sector Listed on the Indonesia Stock Exchange 2019-2023) - Lestari, Firda Maulani; Supriyatna, Yayat; Sari, Maya (Dinasti Publisher, 2024)
This study examined the impact of sustainability and dividend policy on the value of healthcare companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2023. The dependent variable in this analysis was company value, represented by the Price to Earnings Ratio (PER), while the independent variables included sustainability, measured by Return on Assets (ROA), and dividend policy, expressed through the Dividend Payout Ratio (DPR). A linear regression analysis was employed using data derived from the companies' financial statements. The results revealed that sustainability had a significant positive effect on company value, and dividend policy also had a positive contribution. These findings offer valuable insights for both investors and management in formulating financial strategies to enhance the value of healthcare companies. This research is expected to contribute to the growth of financial literature and managerial practices in Indonesia